2023
DOI: 10.1136/tc-2022-057856
|View full text |Cite
|
Sign up to set email alerts
|

What measures are needed to achieve a tobacco endgame target? A Singapore-based simulation study

Abstract: BackgroundAn increasing number of countries are pursuing a tobacco ‘endgame’. We sought to determine the combination of measures it would take to achieve a tobacco endgame in the city-state of Singapore.MethodsUsing an open-cohort microsimulation model, we estimated the impact of existing measures (quit programmes, tobacco taxes, flavours ban) and more novel measures (very low nicotine cap, tobacco-free generation, raising the minimum legal age to 25 years), and combinations thereof, on smoking prevalence in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Singh et al 11 reported that residents of the Solomon Islands would be expected to gain 798 HALYs per 1000 people if smoking was restricted to those ≤20 years of age from 2016 11 . Furthermore, the tobacco endgame goal was predicted to be attained by the TFG alone, which was expected to be more effective than gradually raising the minimum legal age of smoking to 25 years 10 . However, it will take a long time to lower smoking prevalence and reap health gains because current smokers are unaffected by the TFG 10,12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Singh et al 11 reported that residents of the Solomon Islands would be expected to gain 798 HALYs per 1000 people if smoking was restricted to those ≤20 years of age from 2016 11 . Furthermore, the tobacco endgame goal was predicted to be attained by the TFG alone, which was expected to be more effective than gradually raising the minimum legal age of smoking to 25 years 10 . However, it will take a long time to lower smoking prevalence and reap health gains because current smokers are unaffected by the TFG 10,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the tobacco endgame goal was predicted to be attained by the TFG alone, which was expected to be more effective than gradually raising the minimum legal age of smoking to 25 years 10 . However, it will take a long time to lower smoking prevalence and reap health gains because current smokers are unaffected by the TFG 10,12 . Therefore, we suggest introducing the TFG together with aggressive tax increases and implementation of MPOWER policies to end the tobacco epidemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation